(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aims to explore the role of regulatory legislation in curbing the spread of online defamation on the TikTok platform in Saudi Arabia, focusing on three main dimensions of this legislation: the legislative and legal dimension, the procedural and executive dimension, and the supervisory and technical dimension. The study employed a quantitative descriptive-analytical approach, utilizing an online questionnaire to collect data. The sample consisted of 220 TikTok users of varying ages, genders, education levels, and usage duration. The research instrument was a five-point Likert scale questionnaire designed to assess perceptions, knowledge, and behaviors related to legislation and manifestations of defamation. The results demonstrated a strong, statistically significant, positive impact on reducing online defamation across all dimensions of regulatory legislation. The supervisory and technical dimension had the highest impact, followed by the legislative and legal dimension, and then the procedural and executive dimension. The findings also indicated that enhancing the effectiveness of legislation, legal procedures, and technical measures directly contributes to reducing instances of defamation. Furthermore, the study highlighted the importance of integrating legal texts with executive procedures and supervisory technologies to achieve effective user protection.